Can drones be a solution for defibrillation and blood transfusions? A review on the impact of new technologies in emergency healthcare - Akman, Canan; Suzer, Neslihan Ergun; Karcioglu, Ozgur (Frontiers in Disaster and Emergency Medicine, 2024)
Life-threatening arrhythmias, shock and airway compromise represent the most crucial situations to treat in the daily routine of acute medicine. Rapid access to automated external defibrillators (AEDs) and other necessary equipment increases survival rates significantly. The unmanned aerial vehicles (UAV) appear to revolutionize prehospital medicine enabling advanced health care delivery to those in austere environments and difficult regions for both defibrillators and blood products (BP). Although there are still many factors to consider, drone networks show potential to greatly reduce lifesaving equipment travel times for those with cardiac arrest (CA). More research should be performed to fill the gaps in routine practice of operating drones in different clinical scenarios, and geographical variations. As far as delivery of BP via drones, key benefits are minimized risk to human life, cost, speed of delivery and ability to cover areas beyond those of conventional planes. Challenges can be airspace management of BP, decisions on appropriate level of care to deliver during transit and user acceptability. Appropriate integration of drones to ambulances and emergency medical services facilitates efforts to improve healthcare, particularly in difficult and underserved regions. In brief, indications of drone use should be individualized to deliver vital equipment and care to the victim in emergency need, while the effectivity of UAVs must be evaluated case by case basis. This article aims to review the current status of above-mentioned technology and pluses and minuses of UAVs used worldwide, along with future projections.